Bookish people : a novel - Coll, Susan (Harper Muse, 2022)
"A perfect storm of comedic proportions erupts in a DC bookstore over the course of one soggy summer week, punctuated by political turmoil, a celestial event, and a perpetually broken vacuum cleaner"--